Oral organic nanovaccines against bacterial and viral diseases. (August 2022) - Angulo, Carlos; Sanchez, Veronica; Delgado, Karen; Monreal-Escalante, Elizabeth; Hernández-Adame, Luis; Angulo, Miriam; Tello-Olea, Marlene; Reyes-Becerril, Martha
Abstract: Vaccines have saved millions of humans and animals from deadly diseases. Many vaccines are still under development to fight against lethal diseases. Indeed, subunit vaccines are a versatile approach with several advantageous attributes, but they lack strong immunogenicity. Nanotechnology is an avenue to vaccine development because nanoparticles may serve as nanocarriers and adjuvants, which are critical aspects for oral vaccines. This review provides an update of oral organic nanovaccines, describing suitable nanomaterials for oral vaccine design and recent (last five-year view) oral nanovaccine developments to fight against those principal pathogens causing human and animal diseases. Highlights: Organic NPs can be synthetized by emulsification and nanoprecipitation methods. Antigens have been encapsulated in or anchored on NPs to form nanovaccines. In lab animals and target hosts nanovaccines demonstrated immunogenicity. More studies on immmunoprotection by nanovaccines are required. Challenges and perspectives on oral organic nanovaccines are provided.